2018
DOI: 10.1038/s41386-018-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Mice with reduced DAT levels recreate seasonal-induced switching between states in bipolar disorder

Abstract: Developing novel therapeutics for bipolar disorder (BD) has been hampered by limited mechanistic knowledge how sufferers switch between mania and depression-how the same brain can switch between extreme states-described as the "holy grail" of BD research. Strong evidence implicates seasonally-induced switching between states, with mania associated with summer-onset, depression with winter-onset. Determining mechanisms of and sensitivity to such switching is required. C57BL/6J and dopamine transporter hypomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 61 publications
1
64
0
Order By: Relevance
“…While previous studies have found intriguing effects of photoperiod in the dopaminergic system due to photoperiod [29][30][31] , no study has investigated photoperiodic effects due to developmental photoperiod, across multiple stages of development, or in mice that are melatonin competent, such as the C3Hf +/+ strain. In the current study we observed reduced levels of DA and DOPAC for Short winter-like photoperiod mice at P35, thus based on this data and prior work, we hypothesized that the expression of a key dopamine gene, TH, would be decreased for animals raised under Short photoperiodic conditions as well.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have found intriguing effects of photoperiod in the dopaminergic system due to photoperiod [29][30][31] , no study has investigated photoperiodic effects due to developmental photoperiod, across multiple stages of development, or in mice that are melatonin competent, such as the C3Hf +/+ strain. In the current study we observed reduced levels of DA and DOPAC for Short winter-like photoperiod mice at P35, thus based on this data and prior work, we hypothesized that the expression of a key dopamine gene, TH, would be decreased for animals raised under Short photoperiodic conditions as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is the first instance of a molecular and cellular marker based on neurotransmitter phenotype to be associated with vulnerability to stress. Neurotransmitter plasticity, also referred to as neurotransmitter switching (Dulcis & Spitzer, 2012), has been shown to occur in response to other forms of stress such as altered photoperiod exposure (Dulcis et al, 2013;Young et al, 2018) or exposure to psychostimulants such as nicotine (Romoli et al, 2019) and methamphetamine (Kesby et al, 2017) . Interestingly, the change in number of TPH2+ neurons occurred exclusively in the DRv, but not in the other subnuclei of the mid-rostrocaudal DR.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical and functional connectivity of SCN NMS+ neurons suggest that they may have a role in regulating PeVN DA neuron activity 49 . To test whether chronic activation of SCN NMS+ neurons is sufficient to induce the kind of activity-dependent DA plasticity previously observed in the PeVN in response to short photoperiod 37,38 NMS-Cre mice (P85) expressing either Gq-DREADDs or GFP control virus in the SCN received daily clozapine (0.01 mg/kg) or saline injections at ZT17 for 2 weeks while kept in neutral (12L:12D) photoperiod. The mice were then sacrificed (P100) for IHC analysis.…”
Section: Chronic Activation Of Distinct Subsets Of Scn Neurons Regulamentioning
confidence: 99%